MEKANISME PERHITUNGAN DAN PEMUNGUTAN PAJAK PENGHASILAN PASAL 21 PADA KUALITAS PELAPORAN HUMAN CAPITAL MANAGEMENT PT PERKEBUNAN NUSANTARA IV REGIONAL II MEDAN TAHUN 2024 - Diega Arazi Syubhan; Deby Siska Oktavia Pasaribu; Arsyaf Tampubolon (Jurnal Mahkota Bisnis (Makbis), 2026)
This study was conducted at PT Perkebunan Nusantara IV Regional II Medan with the aim of examining and analyzing the calculation and withholding of Article 21 Income Tax (PPh 21) on employees' salaries, as well as evaluating whether the implementation of Article 21 Income Tax at the company complies with the applicable tax regulations. This research employed a descriptive approach using interview results and supporting data related to Article 21 Income Tax obtained from PT Perkebunan Nusantara IV Regional II Medan. The data analysis technique involved conducting field surveys to collect relevant data, analyzing the findings, and comparing the observed practices with established theories and applicable regulations to draw valid conclusions. The results indicate that the calculation and withholding of individual income tax (Article 21 Income Tax/PPh 21) on employees' salaries at PT Perkebunan Nusantara IV Regional II Medan have been implemented in accordance with the applicable tax provisions.